MANAJEMEN PROGRAM NON AKADEMIK DALAM MEWUJUDKAN PRESTASI SISWA ( STUDI MULTI SITUS DI SMP KEMALA BHAYANGKARI 6 SURABAYA DAN SMP WACHID HASYIM 1 SURABAYA ) - syahrul; Amrozi Khamidi; Ainur Rifqi; Yatim Riyanto; Karwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the planning, organizing, implementing, and supervising of non-academic programs in realizing student achievement (multi-site study at SMP Kemala Bhayangkari 6 Surabaya and SMP Wachid Hasyim 1 Surabaya). The main focus of the study is how the planning, organizing, implementing, and supervising of non-academic programs in realizing student achievement at SMP Kemala Bhayangkari 6 Surabaya and SMP Wachid Hasyim 1 Surabaya, the approach used is a qualitative approach with a case study type., the presence of researchers in the middle of the research setting is a must, because researchers in a qualitative study are key instruments for capturing meaning, as well as data collection tools, in this case the researcher will go as far as possible directly to collect the desired data at two sites, namely SMP Kemala Bhayangkari 6 Surabaya and SMP Wachid Hasyim 1 Surabaya. The type of data used in collecting data, researchers are directly related to the source, such as conducting interviews, observing, listening, interpreting, and analyzing. The results of the study show that effective management plays a very important role in fostering students' interests and talents through extracurricular activities. Teachers and mentors play a central role as motivators, facilitators, guides, and evaluators, regularly monitoring and providing feedback to improve students' non-academic achievements. Well-organized activities, communication and collaboration between stakeholders, and adequate facilities and resources are key factors in the success of this non-academic program.